2021
DOI: 10.1108/ijchm-08-2020-0856
|View full text |Cite
|
Sign up to set email alerts
|

Online review helpfulness: the moderating effects of review comprehensiveness

Abstract: Purpose Consumers’ evaluation of online review helpfulness has been widely examined. The extant literature suggests that the attributes of review content (e.g. review length and extremity) influence review helpfulness. However, review length cannot fully reflect the richness of the review content. Anchoring on information diagnosticity and extremity bias, this study aims to explore the effect of review comprehensiveness on its helpfulness. Design/methodology/approach Field observations were obtained from 11,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 67 publications
0
19
0
Order By: Relevance
“…However, no studies, to the best of our knowledge, have attempted to examine how LoS can affect the review-posting behaviors of consumers. Recently, many studies on online reviews in tourism examined factors influencing online review and how they influence hotel strategies and other consumers; however, no studies investigated the relationship between LoS and online reviews (Bortoluzzi et al , 2020; Filieri et al , 2021; Gour et al , 2021; Liu and Hu, 2021; Mariani and Borghi, 2021; Shi and Chen, 2021). The current study examined how different LoS systematically influence consumer review-posting behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…However, no studies, to the best of our knowledge, have attempted to examine how LoS can affect the review-posting behaviors of consumers. Recently, many studies on online reviews in tourism examined factors influencing online review and how they influence hotel strategies and other consumers; however, no studies investigated the relationship between LoS and online reviews (Bortoluzzi et al , 2020; Filieri et al , 2021; Gour et al , 2021; Liu and Hu, 2021; Mariani and Borghi, 2021; Shi and Chen, 2021). The current study examined how different LoS systematically influence consumer review-posting behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…There is broad scholarly consensus that information-search is among the most effective strategies used by individuals to reduce their uncertainty in the decision-making process and attain a sense of security prior to travel (Jonas and Mansfeld, 2017; Liu and Hu, 2021). As consumers form their perceptions of safety out of the information they obtain, their perceived safety depends on how they evaluate that information (Xie et al , 2021) and in this regard there are studies empirically demonstrating the effect of information on tourist perceived safety (Liu-Lastres et al , 2019; Liu et al , 2016a; Xie et al , 2021; Zou and Meng, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…User-generated content (UGC) on social media platforms has recently become an important source of customer behavior in hospitality and tourism research, especially in lodging services (Tsai et al , 2020; Wang et al , 2022), restaurant services (Lee et al , 2021; Li et al , 2020; Liu and Hu, 2021; Pezenka and Weismayer, 2020) and tourism destination contexts (Gour et al , 2021; Taecharungroj and Mathayomchan, 2019). Numerous studies on electronic word-of-mouth (eWOM) have revealed the importance of UGC in customer decision-making (Chakraborty, 2019; Sparks et al , 2013; Tsai et al , 2020; Zhang et al , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%